Implementation of Cosmos/M software in solving electromagnetic field problems I / Mohamad Zulkefli Adam - Adam, Mohamad Zulkefli (1995)
This project concerns with using one of the most recent softwares, namely Cosmos/M. Cosmos/M is designed to solve the problems in the area of electromagnetics in addition to fluid, fatigue, crash, steady state and transient thermal analysis and many more in engineering field. The program is based on finite element method which can operates such as geometry creation, meshing, applying loads and boundary conditions, defining material and section properties, performing the analysis and postprocessing of analysis results.